Is Mild Cognitive Impairment a Precursor of Alzheimer's Disease? Short Review - Janoutová, Jana; Šerý, Omar; Hosák, Ladislav; Janout, Vladimír (Central European journal of public health, 2015)
Mild Cognitive Impairment (MCI) may be a precursor of Alzheimer's disease (AD). There is a boundary area between normal aging and dementia. In practice, the term "age related cognitive decline" has been used interchangeably with "normal aging". Alternatively, the term "aging associated cognitive decline" was introduced and defined by a performance on a standardized cognitive scale focused on learning and memory, attention and cognitive speed, language, or visuoconstructional abilities. The term "mild cognitive impairment" was adopted by Petersen in 2004 to describe a period in the course of neurodegenerative disease where cognition is no longer normal relative to age expectations, however, daily functions are not sufficiently disrupted to correlate with the diagnosis of dementia. Most of the literature refers to the amnestic form of MCI, which is likely a precursor of AD. The rate of conversion from amnestic form of MCI to AD is estimated to reach 10-15% per year. That is why MCI generated a great deal of research. When considering MCI a precursor of AD, it seems reasonable to study AD genetic markers in the MCI patients. In AD, association studies focus on genetic polymorphisms assumed to have an effect on the expression and modulation function of genes associated with AD pathogenesis (ApoE, APP, presenilin 1, presenilin 2, tau protein), and on polymorphisms related to metabolism of the aforementioned proteins (splicing, degradation). Neuropsychological assesment plays a substantial role in the diagnosis of MCI, especially in the case of identification of different MCI subtypes or typical profiles of cognitive performance in prodromal phases of neurodegenerative diseases. The optimal composition of diet may increase an average age and prevent impairment of cognitive functions at the same time. Despite the progress in early diagnosis of MCI and dementia, further research is needed on differential diagnosis and treatment. In amnestic subtype of MCI some genetic markers may already be present, predicting possible future development of AD. Pointing to the need of secondary prevention, lifestyle modifications and possible early treatment could be implemented.
Keywords: secondary prevention; Cognitive Dysfunction; Alzheimer's dementia; Alzheimerova nemoc; genetics; mild cognitive impairment; neuropsychological testing; neuropsychologické testy; Alzheimer Disease; Humans; Neuropsychological Tests; terminology; kognitivní dysfunkce; lidé